Assessing patients with hepatocellular carcinoma meeting the milan criteria: Is liver 3 tesla MR with gadoxetic acid necessary in addition to liver CT?. Issue 4 (30th September 2013) - Cha, Dong Ik; Lee, Min Woo; Kim, Young Kon; Kim, Seong Hyun; Park, Hyun Jeong; Rhim, Hyunchul; Lim, Hyo K.
<x xml:space="preserve">Abstract</x> Purpose To determine the added value of 3 Tesla liver MR in patients with hepatocellular carcinoma (HCC) within the liver computed tomography (CT) ‐based Milan criteria. Materials and Methods Liver CT and MR images of 130 patients with HCC within the Milan criteria based on liver CT were retrospectively reviewed. The number of MR‐diagnosed HCCs and that of high risk hypervascular nodules (HRHNs), the effect of obtaining MR on patient management and CT appearances of MR‐diagnosed HCCs and those of HRHNs were evaluated. Independent predictor for diagnosing additional HCCs on liver MR was analyzed. Results A total of 18.5% (24/130) of patients had additional 39 HCCs on MR, with a 5.4% (7/130) dropout rate from the Milan criteria. 28.5% (37/130) of patients had additional 78 HRHNs. Overall, 39.2% (51/130) of patients required changes in management. The common CT appearances of MR‐diagnosed HCCs were arterial enhancing lesions ≥ 0.5cm (38.4%, 15/39), low density nodules < 1.5 cm (30.8%, 12/39) and invisibility (28.2%, 11/39). For MR‐diagnosed HRHNs, 55.1% (43/78) were invisible on CT. The presence of inconclusive lesions on CT was an independent predictor for diagnosing additional HCCs on MR. Conclusion For patients with HCCs within the Milan criteria on liver CT, liver MR may be necessary to detect additional HCCs and HRHNs. J. Magn. Reson. Imaging 2014;39:842–852. © 2013 Wiley Periodicals, Inc.